Perkembangan Instrumentasi dan Lagu Talempong Kreasi di Sumatera Barat - Indra Yeni (Fakultas Bahasa dan Seni UNP, 2010)
This paper aims to explain the development of musical instruments used in the ensemble of creative talempong and its influence on variations of songs played by these instruments. The development is seen from the musical instruments and the variation songs. The data were collected through a literature study related to the history and development of the ensemble of creative talempong, the musical instruments used, the songs sung and the context of performances that use creative talempong. The finding shows that the development of musical instruments used is tailored to the tastes and culture of local communities. The use of sound system, western musical instruments, and the use of chromatic tones in melody talempong gives an effect on increasing the variety of songs and genres that can be performed with creative talempong. Kata Kunci: creative Talempong, instruments, song